Characterizing third-party logistics setups in the context of construction. Issue 4 (3rd March 2021) - Fredriksson, Anna; Janné, Mats; Rudberg, Martin
Abstract : Purpose: The use of third-party logistics (TPL) setups in construction has increased but is still a new phenomenon. The purpose was to increase understanding of how structural and management dimensions are related in CLSs by describing how CTPL setups are used. Design/methodology/approach: Ten dimensions to describe and structure CLSs were identified from the literature and used to structure a cross-case analysis of 13 Swedish CLSs. Findings: The main findings are: (1) there are three typical initiators of CLSs: municipalities, developers and contractors; (2) CLSs are drivers for service differentiation and modularization among TPL providers as construction specific services are required; (3) CLSs play a new role in construction by coordinating logistics activities between the construction project and the vicinity of the site. Research limitations/implications: The study is based on 13 cases in the Swedish construction context. Additional studies of CLSs in other countries are needed. Practical implications: The ten dimensions can be used as a guide in designing a CLS and in determining the order of design decisions. The identification and structuring of CTPL services also exemplify the variety of service offerings. Originality/value: This is one of the first cross-case analyses of CLSs enabling the characterization of CTPL setups. This study identifies how different services included in the setup relate to the roles of SCM and logistics in construction.